Захист інтересів України у іноземних юрисдикціях за актом про імунітети іноземного суверена - Коваль, Дмитро Олександрович; Коваль, Дмитрий Александрович; Koval, Dmytro O. (My University, 2014)
В статті запропоновано альтернативний до міжнародного форум для пред’явлення претензій Україною до Росії. Висвітлені перспективи звернення до судів США за Актом про імунітети іноземного суверена. Запропоновані маркери для прогнозування ефективності використання зазначеного форуму.

В статье предложен альтернативный международному форум для предъявления претензий Украины к России. Освещены перспективы обращения в суды США по Акту об иммунитетах иностранного суверена. Предложенные маркеры для прогнозирования эффективности использования данного форума.

The occupation of the Autonomous Republic of Crimea by the Russian Federation, the deployment of armed resistance to the lawful demands of authority in the Donetsk and Lugansk regions, cause the discussion of the ways to protect the Ukrainian rights and interests in the international courts and quasijudicial institutions. In this article I concentrate on exploration of the protection of the state interests in the United States courts according to the 1976 Foreign Sovereign Immunities Act. This act codifies the American law on the interpretation of jurisdictional immunities of states and guarantees the right to bring a case to foreign sovereign through the American court. In a laconic and brief form the Ukrainian perspectives of own interests’ protection in the US courts it is possible to summarize by the following: 1. The violation of international law (expropriation and nationalization of the Ukrainian property) and violation of the American citizens rights and rights of persons who work for the United States government by the Russian actions (inter alia as a sponsor of terrorism in Ukraine) can be the subject of the lawsuit in the US court according to the 1976 Foreign Sovereign Immunities Act may be. 2. Implementation of the court decision can be ensured by the property located in the United States. 3. Foreign Sovereign Immunities Act practice currently was applied in more than 500 cases. The mandatory pre-condition for filing a claim against Russia to the American court is a study of such practice. 4. The political risks of a claim may be estimated by the two relatively objective legal categories: political question doctrine and the concept of international balance. Financial risks in the same context may be reduced by the creation of the step-by-step strategy of the Ukrainian interests protection in foreign jurisdictions.
Коваль Д. О. Захист інтересів України у іноземних юрисдикціях за актом про імунітети іноземного суверена / Д. О. Коваль // Український часопис міжнародного права. - 2014. - № 4. - С. 60-65.
Keywords: юрисдикційні імунітети; акт про імунітети іноземного суверена; доктрина міжнародного балансу; захист інтересів України; юрисдикционные иммунитеты; акт об иммунитетах иностранного суверена; доктрина международного баланса; защита интересов Украины; jurisdictional immunities; Foreign Sovereign Immunities Act; the doctrine of international balance; protecting of Ukrainian interests